Behavioral adaptations of human drivers interacting with automated vehicles. (April 2022) - Soni, Shubham; Reddy, Nagarjun; Tsapi, Anastasia; van Arem, Bart; Farah, Haneen
Highlights: Human drivers' interactions with automated vehicles was studied in a field test. Human drivers adapt their driving behaviour when interacting with automated vehicles. Drivers interacting with recognizable automated vehicles adopt smaller critical gaps. After overtaking, drivers merge closer in front of recognizable automated vehicles. Results suggest potential exploitation of automated vehicles by drivers in traffic. Abstract: Advancements in technology are bringing automated vehicles (AVs) closer to wider deployment. However, in the early phases of their deployment, AVs will coexist and frequently interact with human-driven vehicles (HDVs). These interactions might lead to changes in the driving behavior of HDVs. A field test was conducted in the Netherlands with 18 participants focusing on gap acceptance, car-following, and overtaking behaviors to understand such behavioral adaptations. The participants were asked to drive their vehicles in a controlled environment, interacting with an HDV and a Wizard of Oz AV. The effects of positive and negative information regarding AV behavior on the participants' driving behavior and their trust in AVs were also studied. The results show that human drivers adopted significantly smaller critical gaps when interacting with the approaching AV as compared to when interacting with the approaching HDV. Drivers also maintained a significantly shorter headway after overtaking the AV in comparison to overtaking the HDV. Positive information about the behavior of the AV led to closer interactions in comparison to HDVs. Additionally, drivers showed higher trust in the interacting AV when they were provided with positive information regarding the AV in comparison to scenarios where no information was provided. These findings suggest the potential exploitation of AV technology by HDV drivers.